2007
DOI: 10.4152/pea.200804349
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulation of Bray-Liebhafsky (BL) Oscillating Chemical Reaction

Abstract: The computational simulation of the Bray-Liebhafsky (BL) oscillating chemical reaction by differential kinetic methodology is carried out in this work. According to the mechanism of Treindl and Noyes involving 10 reaction steps, the changes of the concentrations of I 2 and O 2 in solution are simulated. When the control parameters are α = 0.55, β = 0.2882 and δ < 0.6, the differential equations present periodic solution, and the oscillations can be observed in 150 min. If α , β and δ are taken as the control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The simulation by mathematics is a simple and effective approach to display the character of nonlinear phenomena for a complex system. In our previous work [22], the concentrations of I 2 (aq) and O 2 (aq) were simulated by involving a two variable model. In order to investigate the BL system more detailed, a four-variable model was used, in which the concentrations I 2 (aq) and O 2 (aq), and the intermediates such as Iand HIO 2 were also calculated by mathematical calculation after proper simplification and modification of the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation by mathematics is a simple and effective approach to display the character of nonlinear phenomena for a complex system. In our previous work [22], the concentrations of I 2 (aq) and O 2 (aq) were simulated by involving a two variable model. In order to investigate the BL system more detailed, a four-variable model was used, in which the concentrations I 2 (aq) and O 2 (aq), and the intermediates such as Iand HIO 2 were also calculated by mathematical calculation after proper simplification and modification of the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Láňová et al based on their first mass spectrometric study confirmed the assumptions made in the N−T model that the escaping rate of oxygen from the solution influences the oscillations substantially and that it needs to be taken into account in the modeling of oscillations. Just recently, Ren et al have also performed computational simulation of the BL reaction based on the N−T mechanism consisting of the above 10 reaction steps and simulated the oscillations of the concentrations of I 2 and of O 2 .…”
Section: Introductionmentioning
confidence: 99%